2019
DOI: 10.3389/ffgc.2019.00059
|View full text |Cite
|
Sign up to set email alerts
|

Increased Nitrogen Availability in the Soil Under Mature Picea abies Trees Exposed to Elevated CO2 Concentrations

Abstract: The response of trees to increasing atmospheric CO 2 concentrations is often mediated by the availability of nutrients. However, little is known about the influence of CO 2 enrichment on nutrient availability in forests with mature trees. We studied processes in the soil under five 35-m-tall Norway spruce trees (Picea abies) in NW Switzerland that were exposed to a mean CO 2 concentration of 550 ppm for 5 growing seasons using free air CO 2 enrichment (FACE). We compared them with values from the soil under fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…The weak or missing N cycle response under FACE treatment in some ecosystems -grassland, heathland or forest observed here and elsewhere (Wild et al 2018;Schleppi 2019;Rütting 2020), could be due to limitation of another nutrient, such as P (Dijkstra et al 2013;. At EucFACE, evidence derived from Eucalyptus leaf C:N:P stoichiometry revealed strong P re-translocation compared to N in both ambient and CO 2 treated trees (Crous et al 2019), emphasising that P is highly limiting for the trees in this ecosystem.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The weak or missing N cycle response under FACE treatment in some ecosystems -grassland, heathland or forest observed here and elsewhere (Wild et al 2018;Schleppi 2019;Rütting 2020), could be due to limitation of another nutrient, such as P (Dijkstra et al 2013;. At EucFACE, evidence derived from Eucalyptus leaf C:N:P stoichiometry revealed strong P re-translocation compared to N in both ambient and CO 2 treated trees (Crous et al 2019), emphasising that P is highly limiting for the trees in this ecosystem.…”
Section: Discussionmentioning
confidence: 46%
“…Beginning with photosynthesis, CO 2 can stimulate a cascade of potential effects in an ecosystem, leading to an increase in plant growth and in belowground allocation (root growth) (Andresen et al 2016b;Körner 2018). Subsequently, increased rhizodeposition could stimulate organic matter decomposition (rhizosphere priming) and nutrient mineralization, leading to increased nutrient availability, to meet the extra nutrient demand (Dijkstra et al 2013;Kuzyakov 2015;Jilling et al 2018;Moreau et al 2019;Schleppi 2019). A meta-analysis found that gross N mineralization rate was stimulated by CO 2 across N limited ecosystems, but not in ecosystems limited by P , potentially because the cascade response to labile C deposition switches from N mining to P mining (Dijkstra et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively short incubation periods are then applied, in the order of magnitude of one day (e.g. Wessel and Tietema, 1992;Schleppi et al, 2019). Instead, the aim of field studies is to describe the overall fate of the applied tracer.…”
Section: Experimental Designmentioning
confidence: 99%
“…Interestingly, the importance of both genera to plants has been verified in multiple metagenomic studies ( Loper et al, 2012 ; Mendes et al, 2013 ), however, the interplay between these important root bacteria and forest trees remains a mystery. In the forest soil, root exudation is suspected to enhance rhizobacteria, in turn leading to increased decomposition of soil organic matter, that is, increased C mineralization, a process termed microbial priming ( Schleppi et al, 2019 ). Here, we use this term on a wide perspective, even that P release from soil phosphates, for example, is not strictly considered as priming ( Dijkstra et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%